2017
DOI: 10.1016/j.virol.2017.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the human papillomavirus type 16 late promoter by transcriptional elongation

Abstract: Transcripts from the late promoter of human papillomavirus type 16 (HPV16) are upregulated upon host cell differentiation. Differentiation-dependent transcript regulation is thought to sequester viral antigens in the uppermost epithelial layers, facilitating immune evasion. The mechanisms regulating late promoter upregulation during differentiation are poorly characterized. We show that the late promoter is upregulated at the transcriptional level and that the viral enhancer stimulates promoter activity. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 93 publications
(204 reference statements)
0
21
0
Order By: Relevance
“…However, speculating about the mode of L1 isoform regulation, the following scenario could be envisioned: late PV transcripts are known to be strongly upregulated upon keratinocyte differentiation. However, due to insufficient suppressed late viral promoter activity, late transcripts can already be detected in undifferentiated cells ( Songock et al, 2017 ). Indeed, in contrast to mucosal types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, speculating about the mode of L1 isoform regulation, the following scenario could be envisioned: late PV transcripts are known to be strongly upregulated upon keratinocyte differentiation. However, due to insufficient suppressed late viral promoter activity, late transcripts can already be detected in undifferentiated cells ( Songock et al, 2017 ). Indeed, in contrast to mucosal types (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the LIP (Liver-enriched Inhibitory Protein) and LAP (Liver-enriched Activator Protein) isoforms of C/EBPα have been shown to regulate late promoter activity [ 41 ]. More recent studies have shown that transcription elongation regulates late promoter activity through the recruitment of elongation mediators (e.g., CDK8, BRD4) to viral genomes upon differentiation [ 42 ]. Late gene expression is also regulated by alternative splicing and changes in polyadenylation site usage [ 16 ].…”
Section: Regulation Of Viral Gene Expression Upon Keratinocyte Difmentioning
confidence: 99%
“…Although RNA polymerase II is bound at the late promoter in undifferentiated keratinocytes, elongation is inefficient and does not progress to the late region. In contrast, in differentiated cells, the enhancer recruits members of the BET family proteins—including Brd4 and its binding partner CDK8—to the Mediator complex to stimulate transcription elongation [ 48 ]. Changes in signaling during keratinocyte differentiation must also regulate the late promoter, for example PKCδ [ 49 ] has been shown to activate it.…”
Section: Viral Late Promoter Activitymentioning
confidence: 99%